2005
DOI: 10.1080/019021490927088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quercetin Supplementation on Lung Antioxidants After Experimental Influenza Virus Infection

Abstract: In the mice, instillation of influenza virus A/Udorn/317/72(H3N2) intranasally resulted in a significant decrease in the pulmonary concentrations of catalase, reduced glutathione, and superoxide dismutase. There was a decrease in vitamin E level also. These effects were observed on the 5th day after viral instillation. Oral supplementation with quercetin simultaneous with viral instillation produced significant increases in the pulmonary concentrations of catalase, reduced glutathione, and superoxide dismutase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 42 publications
5
48
0
1
Order By: Relevance
“…Nonetheless we have observed that the preventive treatment with 10 mg/kg PC modulated the excessive generation of the two enzymes both in the lungs and livers of IAV-infected animals (unpublished). Similar results were obtained by Kumar et al (2005); they detected a rise of lung antioxidant enzymes during EIVI and reported that oral supplementation with quercetin increased their pulmonary concentrations. The application of HL-SOD caused a reduction of lung SOD and CAT levels at each time point.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Nonetheless we have observed that the preventive treatment with 10 mg/kg PC modulated the excessive generation of the two enzymes both in the lungs and livers of IAV-infected animals (unpublished). Similar results were obtained by Kumar et al (2005); they detected a rise of lung antioxidant enzymes during EIVI and reported that oral supplementation with quercetin increased their pulmonary concentrations. The application of HL-SOD caused a reduction of lung SOD and CAT levels at each time point.…”
Section: Discussionsupporting
confidence: 75%
“…The presented results together with our previous data (Murzakhmetova et al, 2008) show that infl uenza A/Aichi virus infection is accompanied with defi cits in antioxidant enzyme activities and an increase in ROS and lipid peroxidation (LPO) levels in the lungs, livers, and sera, which can be overcome through supplementation with antioxidants. Plant polyphenols acting as antioxidants also demonstrate protective effects during IAV-triggered oxidative stress (Kumar et al, 2005;Murzakhmetova et al, 2008). It has been also demonstrated that treatment with SOD improves lung pathology and reduces lethality in IAV-induced pneumonia (Angelova et al, 2001;Oda et al, 1989).…”
Section: Discussionmentioning
confidence: 98%
“…These changes in AOE expression was also observed in a mouse model of hMPV infection [11]. Such an increase in SOD 2 expression and decreased expression of catalase, as well as decreased GSH/GSSG ratio, has also been reported in influenza infection both in vitro and in vivo [64][65][66]. Taken together, this information suggests that airway oxidant-antioxidant imbalance could play a very important role in the pathogenesis of RSV-induced lung disease and possibly other respiratory viral infections.…”
Section: Potential Regulatory Mechanism Of Aoe Expression In Rsv Infesupporting
confidence: 55%
“…Antioxidants (glutathione, vitamins, beta-carotene, selenium and flavonoids) as dietary support or pharmacological treatment can be a promising approach. Great attention has been focused on flavonoids [16,17], polyphenolic compounds with antioxidant, anti-inflammatory and antibacteric activity, hugely present in fruits and vegetables. Among natural flavonoids, naringin (N, Fig.…”
Section: Aerosolized Antioxidant and Anti-inflammatory Agents In Cystmentioning
confidence: 99%